The Woman Who Changed her Brain: Unlocking the Extraordinary Potential of the Human Mind by Barbara Arrowsmith-Young - Davidson, Michael (Journal of Scientific Exploration, 2012)
<!--[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} --> <!--[endif] -->This book describes the difficulties experienced by Barbara Arrowsmith-Young of growing up with severe learning difficulties; the means whereby she found the techniques, not to live with those difficulties, but to actually address and resolve them; and how she has brought those techniques to children and adults through her 35 Arrowsmith Schools now established in various parts of Canada and the U.S. Barbara grew up in Peterborough, Ontario, where for the first 26 years of her life, she “lived in a fog.” She could make no sense of the relationship between the hour and minute hands of a clock, so could not tell the time. She could not add or subtract double-digit numbers; had difficulty reading; got the wrong words for common objects; could not tell the difference between the right and left hands; was accident-prone; kept getting lost; and could not tie her shoelaces. Barbara could however remember (parrot) accurately the 9 o’clock news and was evidently gifted with a remarkable memory and sense of determination. These abilities got her through school and university. The change came in graduate school when she happened across Alexander Luria’s 1972 classic The Man with the Shattered World: The History of a Brain Wound which described the cognitive deficits of a brain-injured soldier from WWII. Barbara identified with the soldier among whose difficulties was the inability to tell time following his brain injury. Around the same time she came across some work by Mark Rosenzweig (Rosenzweig, Love, & Bennett 1968) which demonstrated that the brains of rats could physically change in response to stimulation. If it was possible for rat brains to change, then maybe it was possible for human brains to change also.